A fluorescence and photoactivity dual-activatable prodrug with self-synergistic magnification of the anticancer effect. (14th May 2019) - Li, Jun; Ni, Xiang; Zhang, Jingtian; Liang, Yong; Gao, Zhiyuan; Zhang, Xiaoyan; Zheng, Donghui; Ding, Dan
Abstract : A hydroxycamptothecin prodrug is developed, which can self-report the drug distribution and achieve self-synergistic anticancer efficacy through oxidation therapy. Abstract : Reducing the chemo-resistance of cancer cells or making cancer cells sensitive to chemo-drugs plays a key role in boosting the efficacy of cancer chemotherapeutics in the clinic. Aiming for this, we develop a fluorescence and photoactivity dual-activatable prodrug (HCA–SS–HCPT) consisting of an aggregation-induced emission luminogen (AIEgen) named HCA (4-dimethylamino-2′-hydroxychalcone), a disulfide bond linker (–SS–), and the anticancer chemo-drug hydroxycamptothecin (HCPT). HCA–SS–HCPT is then formulated into nanoparticles with an average size of about 126 nm, which are weakly emissive and generate negligible reactive oxygen species (ROS) in aqueous media due to the quenching effect of the conjugated HCPT. In the presence of glutathione, whose concentration inside cancer cells is >1000-fold higher than that in blood, the –SS– is cleaved and then intact HCPT and HCA are simultaneously released, leading to restoration of the fluorescence and ROS generation capacity of HCA. Both in vitro and in vivo studies demonstrate that the cleaved HCA can not only track the co-delivered HCPT, but also more importantly, serve as a non-toxic pro-oxidant by production of a small amount of ROS under light irradiation to make four kinds of cancer cells much more susceptible to HCPT through oxidation therapy, thus achieving significant synergistic enhancement of anticancer efficacy.